A novel class of inhibitors that target SRSF10 and promote p53-mediated cytotoxicity on human colorectal cancer cells. Issue 2 (25th May 2021) - Sohail, Muhammad; Shkreta, Lulzim; Toutant, Johanne; Rabea, Safwat; Babeu, Jean-Philippe; Huard, Caroline; Coulombe-Huntington, Jasmin; Delannoy, Aurélie; Placet, Morgane; Geha, Sameh; Gendron, Fernand-Pierre; Boudreau, François; et al.
Abstract: The elevated expression of the splicing regulator SRSF10 in metastatic colorectal cancer (CRC) stimulates the production of the pro-tumorigenic BCLAF1-L splice variant. We discovered a group of small molecules with an aminothiazole carboxamide core (GPS167, GPS192 and others) that decrease production of BCLAF1-L . While additional alternative splicing events regulated by SRSF10 are affected by GPS167/192 in HCT116 cells (e.g. in MDM4, WTAP, SLK1 and CLK1 ), other events are shifted in a SRSF10-independent manner (e.g. in MDM2, NAB2 and TRA2A ). GPS167/192 increased the interaction of SRSF10 with the CLK1 and CLK4 kinases, leading us to show that GPS167/192 can inhibit CLK kinases preferentially impacting the activity of SRSF10. Notably, GPS167 impairs the growth of CRC cell lines and organoids, inhibits anchorage-independent colony formation, cell migration, and promotes cytoxicity in a manner that requires SRSF10 and p53. In contrast, GPS167 only minimally affects normal colonocytes and normal colorectal organoids. Thus, GPS167 reprograms the tumorigenic activity of SRSF10 in CRC cells to elicit p53-dependent apoptosis. Graphical Abstract: